Synopsis of the genus Pandrosos Bates, 1867 (Coleoptera, Cerambycidae) - Mermudes, José Ricardo M.; Napp, Dilma Solange (Zootaxa, 2009)
Pandrosos Bates, 1867 is a formerly monotypic South American genus containing the type species, P. phtisicus (Klug, 1825). A second species, P. proximus Mermudes & Napp sp. nov., described from Brazil (Mato Grosso), is added to the genus. Redescription of the genus and of the type species are also provided.